Happiness and health care coverage - David G. Blanchflower (Institute for the Study of Labor (IZA), 2009)
In this paper I examine the characteristics of adults who report on whether they have health care coverage and of people who say that they are unable to see a doctor over the preceding year because of the cost. I make use of a unique data set, the Behavioral Risk Factor Surveillance System, a phone survey undertaken in the United States for the years 2005-2009. I find evidence that not having the ability to see a doctor because of an inability to pay is a major and substantial source of unhappiness in the United States, even for people with high income.
Keywords: I18; 330; Life satisfaction; health care coverage; Gesundheitsversorgung; Krankenversicherung; Lebenszufriedenheit; USA